Child-friendly procedures and accommodations for the use of a self-report fear survey with children who have visual impairments: Reflections on a South African case study. (September 2014) - Visagie, Lisa; Loxton, Helene
Although the experience of childhood fear has been deemed a common phenomenon, in some cases, children's fears can become excessive and interfere with daily functioning and activities, and may thus warrant clinical attention. It is in cases such as these that reliable and valid methods to assess childhood fears are required. Although normative fear literature describes many effective modes of assessment, these methods are not accessible to all children, and certain accommodations are necessary when assessing the fears of children with visual impairments. This article provides a reflection on a case study where the fears of 67 South African children with varying degrees of visual impairment were assessed using the South African version of the Fear Survey Schedule for Children (FSSC-SA). Aspects relating to child-friendly procedure and accommodations are discussed.